Solid angles and Seifert hypersurfaces - Maciej Borodzik (2020)
© 2020, The Author(s). Given a smooth closed oriented manifold M of dimension n embedded in Rn+2, we study properties of the ‘solid angle’ function Φ: Rn+2\ M→ S1. It turns out that a non-critical level set of Φ is an explicit Seifert hypersurface for M. This gives an explicit analytic construction of a Seifert surface in higher dimensions.